Thoracic vertebra fixation with a novel screw-plate system based on computed tomography imaging and finite element method. (April 2020) - Zhang, Wencan; Zhao, Junyong; Jiang, Xiujuan; Li, Le; Yu, Chenxiao; Zhao, Yuefeng; Si, Haipeng
Highlights: This is the first study to compare the biomechanical advantages between the new pedicle screw-plate orthopedic internal fixation system and traditional pedicle screw-rod orthopedic internal fixation system by the finite element method. The novel pedicle screw-plate internal fixation system has lower profile in orthopedics. The novel pedicle screw-plate internal fixation system has higher strength when comparing with the traditional pedicle screw-rod orthopedic internal fixation system. The novel spine pedicle screw-plate system can be used as a new internal fixation and provide better comfort for patients. Abstract: Background and objective: The traditional pedicle screw-rod internal fixation system has been widely used for thoracic diseases in clinical practice, but its high profile increases the damage to soft tissue, leading to long-term intractable back stiffness. The purpose of this study is to compare biomechanical advantages between the new spine pedicle screw-plate internal fixation system and traditional pedicle screw-rod internal fixation system using finite element analysis. Methods: Based on computed tomography (CT), four three-dimensional finite element models of T7-T9 were constructed. The downward concentrated force of 150 N and the moment of 5 Nm was applied to the models to simulate six physiological activities, including flexion, extension, left and right lateral bending, left and right axial torsion. The maximum displacement, range of motion (ROM) and maximum stress of the two models in six physiological activities, was measured to evaluate the biomechanical advantages of the novel pedicle screw-plate internal fixation system. Results: The novel pedicle screw-plate internal fixation system has a lower profile than the traditional pedicle screw-rod internal fixation system. With regards to the stability, the maximum displacement of the models of two internal fixation systems decreased by 56.2%–91.4% under the six motion status when comparing with the unstable model. Meanwhile, the ROM remained unchanged between the two models of internal fixation systems besides the left lateral bending. However, there is no significant difference in the ROM between the models of the two internal fixation systems in left lateral bending motion ( P  = 0.203). In terms of the strength, the maximum stress in the model with the new pedicle screw-plate internal fixation system was higher than that of model with the traditional pedicle screw-rod internal fixation system in every motion status but left and right lateral bending motion. Conclusions: The novel pedicle screw-plate internal fixation system has lower profile in orthopedics and higher strength, However, it has no disadvantage when comparing with the traditional pedicle screw-rod internal fixation system in terms of the stability. In summary, we suggest that the novel spine pedicle screw-plate system can be used as a new internal fixation and provide better comfort for patients.